Analoging the digital: Designing better binary option contracts. Issue 4 (20th September 2021) - Tian, Yisong S.
Abstract: Binary option pays a fixed dollar amount if it matures in the money and nothing otherwise. While this cash‐or‐nothing payoff structure is very attractive to speculators, it also creates incentives to manipulate the underlying asset price in order to gain extra payoff. In this paper, we propose better designs for binary options that disincentivize market manipulation and highlight two key features of such designs. We demonstrate the effectiveness of the new contract designs using numerical examples.